Pemodelan Kondisi Perkerasan Jalan dengan Metode Probabilistik Rantai Markov - Edison Pardamean Togatorop; Ahmad Perwira Mulia Tarigan; Emma Patricia Bangun (Jurnal Syntax Admiration, 2023)
Road pavements are an important part of transportation infrastructure and require regular maintenance. This study aimed to model the condition of road pavement by the probabilistic method of Markov chains. The method used in this study is a literature study and data collection from a survey of road pavement conditions in the field. Data analysis was performed using the Markov chain probabilistic method, which can be used to model changes in pavement conditions over time. The results showed that the Markov chain probabilistic method can be used to model changes in pavement conditions with high accuracy. This method can also be used to make predictions of future pavement conditions and determine the right time to perform maintenance and repairs. The study recommends using the Markov chain probabilistic method as a tool to model pavement conditions and make appropriate maintenance and repair decisions. Thus, it is expected to increase the effectiveness of road pavement management and extend the service life of road pavement.